Undifferentiated osteosarcoma of the mandible oblique line: a case report. - Camargo, Angela Jordão; Cheade, Mayara; Martinelli, Celso; Watanabe, Plauto Christopher Aranha (Brazilian Dental Science, 2015)
Osteosarcoma (OS) is the most common primary malignant tumor of bone. However, osteosarcoma located in the jaw (JOS) is rare, aggressive and malignant, constituting 5% to 13% of all cases of skeletal OS. JOS has a male predilection with 34 to 36 years old. Prognostic is associated with several variables, such as tumor location, initial size, existence or absence of metastasis, gender, age, cytogenetic chances and respond to chemotherapy. We report the unusual case of osteosarcoma in the mandible on retromolar area arising from primitive bone forming mesenchyme; most often arises in the metaphysis of long bones of the extremities.